Obesogenic behaviour in school-age children: A cross-sectional study - Akifah Syahrir; Akbar Harisa; Nur Fadilah; Yodang Yodang (Palembang MediRose Publisher, 2024)
Background: Obesogenic behaviour, characterized by a lack of physical activity, extended periods of watching television, and insufficient consumption of nutritious food, significantly contributes to the risk of obesity in children. The highlights the importance of addressing these behavioural risk factors to combat the growing trend of childhood obesity.Objective: To determine the characteristics of obesogenic behaviour in school-age children in Makassar City.Methods: This study used quantitative research with a cross-sectional design. This research was conducted from July to September 2021 in three elementary schools located in Makassar. The research used purposive sampling for participant selection, and data collection was carried out using questionnaires completed by the respondents. For data analysis, the study applied spearman correlation and chi-square tests. Results: In this study involving 209 students, predominantly male (50.7%), 11 years old (46.4%), living in urban areas (56%), and overweight (54.1%), the spearman correlation test revealed a strong correlation between BMI (p=0.005) and obesogenic behaviour. Additionally, the chi-square test indicated significant associations of gender (p=0.027) and living region (p=0.012) with obesogenic behaviour.Conclusion: The study found a significant relationship between gender, domicile, BMI, and nutritional status, and their impact on children’s obesogenic behaviour. These findings underline the importance of further research with a larger sample size of elementary school students to explore additional characteristics influencing obesogenic behaviours.